Unia Europejska a religia - Golus, Aleksandra (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The founding fathers of EU wanted to build a united Europe, which would be based on Christian values. However, they saw also the need to separate the secular authority from the religious. Therefore, it seems to be very interesting to examine how this question have been solved. The aim of the article is to present an attitude of the European Union toward religion over the past few decades, as well as to analyze the dynamics of relations between the EU - Church and guarantees that the EU provides to individuals in the area of freedom of religion.